A review of recent research on cognitive, metacognitive and affective aspects of problem solving - Barkatsas , Anastasios N.; Hunting, Robert P. (NOMAD Nordic Studies in Mathematics Education, 1996)
Mathematical problem solving is a complex activity that necessitates thoughtful consideration about the best ways to teach it, since any two individuals can arrive at the same solution to a problem using different, but correct methods. An identification of common traits that expert problem solvers possess, instruction related problem solving research, the contribution of cognition, meta-cognition and belief systems, are presented in this research review in an effort to weave a coherent picture of the state of the art of problem solving in mathematics today. Some unrepresented and underrepresented issues are also considered, in order to provide evidence of the diversity and multiplicity of issues concerning mathematical problem solving research and the need for collaboration between researchers in this field of study.